Do Epigenetic Timers Control Petal Development? - Huang, Ruirui; Huang, Tengbo; Irish, Vivian F. (Frontiers in Plant Science, 2021)
Epigenetic modifications include histone modifications and DNA methylation; such modifications can induce heritable changes in gene expression by altering DNA accessibility and chromatin structure. A number of studies have demonstrated that epigenetic factors regulate plant developmental timing in response to environmental changes. However, we still have an incomplete picture of how epigenetic factors can regulate developmental events such as organogenesis. The small number of cell types and the relatively simple developmental progression required to form the Arabidopsis petal makes it a good model to investigate the molecular mechanisms driving plant organogenesis. In this minireview, we summarize recent studies demonstrating the epigenetic control of gene expression during various developmental transitions, and how such regulatory mechanisms can potentially act in petal growth and differentiation.